2021
DOI: 10.3390/nu13082788
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylactic Effects of Glutamine on Muscle Protein Synthesis and Degradation in Rats with Ethanol-Induced Liver Damage

Abstract: The purpose of this research was to investigate the prophylactic effects of glutamine on muscle protein synthesis and degradation in rats with ethanol-induced liver injury. For the first 2 weeks, Wistar rats were divided into two groups and fed a control (n = 16) or glutamine-containing diet (n = 24). For the following 6 weeks, rats fed the control diet were further divided into two groups (n = 8 per group) according to whether their diet contained no ethanol (CC) or did contain ethanol (CE). Rats fed the glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…In the present study, no differences were noted in a-diversity among the groups (Figure 4). This result is consistent with those of our previous studies [22,26,37]. However, compared with other studies, the ratio of fecal firmicutes to bacteroidetes and a-diversity in the ethanol-fed animals of the present study was not concordant because of differences in the administration routes, feeding durations, and animal species [38][39][40].…”
Section: Intestinal Damage and Egfsupporting
confidence: 91%
“…In the present study, no differences were noted in a-diversity among the groups (Figure 4). This result is consistent with those of our previous studies [22,26,37]. However, compared with other studies, the ratio of fecal firmicutes to bacteroidetes and a-diversity in the ethanol-fed animals of the present study was not concordant because of differences in the administration routes, feeding durations, and animal species [38][39][40].…”
Section: Intestinal Damage and Egfsupporting
confidence: 91%
“…SLC1A5 is known as a transporter of alanine, serine, and cysteine but transports glutamine in a Na + -dependent manner in the liver ( Scalise et al, 2018 ). A comparison of rats fed a high-alcohol diet either supplemented with glutamine (at 0.84%) or not indicated that hepatic fat deposition, inflammation, altered liver function, and hyperammonemia in the glutamine group were all attenuated ( Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…When duodenal damage was examined, we showed that acute ethanol administration caused loss of epithelial cells in the villus tips and bleeding in the mucosa. Studies in rodents and humans have shown that the morphological changes induced by ethanol in the liver are characterized by steatosis, necrosis, fibrosis, mononuclear cell infiltration, hyperemia, dilatation of sinusoids, various degrees of degeneration of hepatocytes (swelling, vacuolization and hydropic degeneration), and Kupffer cell hyperplasia [20][21][22][23]. Moreover, morphological examinations in experimental animal models have reported that oral or intragastric ethanol intake poses a risk of bleeding in the gastric and duodenal mucosa.…”
Section: Discussionmentioning
confidence: 99%